43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-699
|View full text |Cite
|
Sign up to set email alerts
|

Flow Visualization with Laser-Induced Thermal Tufts

Abstract: The laser-induced thermal tuft is a new flow visualization technique for simulating traditional tufts with a thermal plume. A laser is used to heat a point of interest on a windtunnel model, causing downstream convection of thermal energy from the heated spot. A temperature-sensitive coating is used to visualize the thermal plume. This technique can be used to indicate flow direction, locate regions of separated flow, and detect laminar/turbulent transition. One primary advantage of thermal tufts is that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Their measurements show the length of the thermal tuft at a fixed axial position on a flat plate increasing with increasing velocity. This trend is in the opposite direction of the measurements presented by Gregory and Peterson [3] and Baughn et al [13], in which the tuft length decreased when the velocity increased. The reason for the opposite trend reported by Hunt and Pantoya [12] is unknown.…”
contrasting
confidence: 57%
See 4 more Smart Citations
“…Their measurements show the length of the thermal tuft at a fixed axial position on a flat plate increasing with increasing velocity. This trend is in the opposite direction of the measurements presented by Gregory and Peterson [3] and Baughn et al [13], in which the tuft length decreased when the velocity increased. The reason for the opposite trend reported by Hunt and Pantoya [12] is unknown.…”
contrasting
confidence: 57%
“…An experimental test of the shear stress dependency was performed to validate the theory and help resolve the discrepancy between the results of Gregory and Peterson [3] and Hunt and Pantoya [12]. Gregory and Peterson [3] reported that tuft length decreases with velocity, whereas Hunt and Pantoya [12] reported results of the opposite trend.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations